Core Values in Nursing Care Based on the Experiences of Nurses Engaged in Neonatal Nursing: A Text-mining Approach for Analyzing Reflection Records - Watanabe, Hiromi (Yonago Acta Med, 2018)
BACKGROUND: Strong feelings about and enthusiasm for nursing care are reflected in nurses’ thoughts and behaviors in clinical practice and affect their profession. This study was conducted to identify the characteristics of core values in nursing care based on the experiences of nurses engaged in neonatal nursing through a process for recognizing the conceptualization of nursing. METHODS: We conceptualized nursing care in 43 nurses who were involved in neonatal nursing using a reflection sheet. We classified descriptions on a sheet based on the Three-Staged Recognition scheme and analyzed them using a text-mining approach. RESULTS: Nurses involved in neonatal nursing recognized that they must take care of the “child,” “mother,” and “family.” Important elements of nursing in nurses with less than 5 years versus 5 or more years of neonatal nursing experience were classified into seven clusters, respectively. These elements were mainly related to family members in both groups. In nurses with less than 5 years of experience, four clusters of one-way communication by nurses were observed in the analysis of the key elements in nursing. On the other hand, five clusters of mutual relationships between patients, their family members, and nurses were observed in nurses with 5 or more years of experience. CONCLUSION: In conclusion, the core value of nurses engaged in neonatal nursing is family-oriented nursing. Nurses with 5 or more years of neonatal nursing experience understand patients and their family members well through establishing relationships and providing comfort and safety while taking care of them.